2020
DOI: 10.33736/bjrst.2022.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dragonflies in Bawean Island Nature Reserve, Indonesia

Abstract: Bawaean Island is known for its endemic Bawa deer and other vertebrate species of mammals, avians and reptiles. However, little is known about the invertebrates, especially the Odonata (dragonflies) group. The aim of this study was to examine the variety of dragonflies on the Bawaean Island. The observation method was employed for data collection while the Shannon-Weinner Diversity Index was used for data analysis. A total of 23 dragonflies’ species consisting of four families were collected throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Koneri et al (2020) found that the number of individuals of the O. sabina and P. flavescens species increased along with reduced canopy. These two species are generally found to be abundant in open areas despite disturbances in the form of human activity (Leksono et al 2017;Perez and Bautista 2020;Rohman et al 2020). This proves that they are habituated to these anthropogenic environments.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Koneri et al (2020) found that the number of individuals of the O. sabina and P. flavescens species increased along with reduced canopy. These two species are generally found to be abundant in open areas despite disturbances in the form of human activity (Leksono et al 2017;Perez and Bautista 2020;Rohman et al 2020). This proves that they are habituated to these anthropogenic environments.…”
Section: Discussionmentioning
confidence: 90%
“…There were 46 species of dragonflies found (Potapov et al 2020). In general, the species richness of dragonflies in the Lesser Sunda Islands (including Lombok) tends to be lower than in other regions (Koneri et al 2020;Rohman et al 2020;Sugiman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The placement of Bawean Island between Kalimantan and Java reveals that this region has distinct biogeography. The terrain is uneven, hilly to mountainous, and it has an ecosystem like a tropical lowland rainforest (Rohman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%